Design analysis of compact autonomous railway inspection vehicle (CARIV) - Bahar, Mohd Bazli; Mohd Aras, Mohd Shahrieel; Lim, Zhi Han; Ho, Gui Yan; Teo, Seng Long; Sulaiman, Marizan; Abdul Azis, Fadilah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The aim of this project is to reduce the occurrence of train derailment due to railway track defects to zero in the following years by increasing the efficiency of railway track inspection and railway track defects detection. Moreover, this project aims to reduce the need of railway track inspection workers to perform on-foot inspection at odd hours. All of these can be achieved by deploying the compact autonomous railway inspection vehicle (CARIV). The CARIV is equipped with ultrasonic sensors, which will be used to detect railway track defects. In addition, when railway track defects are detected, CARIV will take an image of the defective section of the railway track and send to the operator together with the GPS coordinates via email. CARIV will also be providing live video feedback to a browser so that the operator is able to perform visual checking for railway track defects undetectable by the ultrasonic sensor without having to perform on-foot inspection. This is to allow the operator to inspect the railway track defect in detail to determine the seriousness of the railway track damage. The final phase of this project is to test the system on fabricated railway track with defects.